FACTOR ASSOCIATED TO DAIRY MILK STORAGE BY WORKING MOTHER’S IN SOSIAL PUBLIC HEALTH CENTER - Amelia Putri Habsari; Chairil Zaman; Helen Evelina (Majalah Kedokteran Sriwijaya, 2022)
Mothers can prepare “Dairy Milk Mother’s Savings”. An understanding of the importance of Dairy Mother's Milk saving must be supported by her husband and the surrounding environment because mothers can prepare themselves in prioritizing the health of babies with breast milk that has been dairy. This study aims to determine the factors associated with dairy breastmilk storage by worked mothers in work area at the Sosial Health Center Social in Palembang. This study uses a quantitative analytic survey research design with a cross sectional approach. The population of this study were babies who received exclusive breastfeeding totaling 475 babies. The minimum research sample in this Sukajaya village is 343 babies from 17 posyandu. The sampling technique uses accidental sampling. Interview data collection method using a questionnaire. Data analysis was done by Chi square test of 95% confidence level (? = 0.05). The results of this study indicated there were an associated between knowledge (? = 0.011), occupation (? = 0.003), education (? = 0.030), husband's support (? = 0.043) and health promotion (? = 0.024), there were no between relationship attitude (? = 0.341) and age (? = 0.246) with dairy milk storage by the mother of the worker. It was recommended to the Health Center can be taken into consideration made decision carrying counseling.